Multilingual education for social justice : globalising the local - International Conference on Multilingual Education: Challenges, Perspectives, and Opportunities (2008 : Zakir Husain Centre for Educational Studies); Mohanty, Ajit K.; Panda, Minati; Phillipson, Robert; Skutnabb-Kangas, Tove; UNICEF (New Delhi : Orient Blackswan, 2009)
Contributed papers presented at the International Conference on Multilingual Education: Challenges, Perspectives, and Opportunities, held at the Zakir Husain Centre for Educational Studies, Jawaharlal Nehru University, New Delhi in February 2008, organized by UNICEF and others.
Includes bibliographical references (p. [343]-385) and index.
Keywords: MULTICULTURAL EDUCATION -- CONGRESSES; LANGUAGE AND EDUCATION -- CONGRESSES; MULTILINGUALISM -- SOCIAL ASPECTS -- CONGRESSES